Polski eurosceptycyzm w kontekście dylematów teoretycznych i porównawczych (Politeja, 2015)
Polish Euroscepticism in the context of theoretical and comparative dilemmasThe aim of this article is an analysis of two of the most inflammatory issues in the debate over Euroscepticism – the typology of anti‑European attitudes and the main conditioning factors of these attitudes. The first aspect constitutes a certain substitute for a definitional debate, since despite the abundance of studies related to Euroscepticism, such studies contain only trace definitional concepts. In the Polish perspective, the two issues above have been presented in the context of the specificity of Poland’s political scene in the 1990s and early 2000s. This confirms that Euroscepticism is a phenomenon that exceeds the scope of simple generalizations, and is characterized by specific and unique processes occurring on the scale of particular countries. It should be acknowledged that, in Poland, we are dealing with a relatively clear scheme in which Euroscepticism relates almost exclusively to right‑wing parties. This does not mean, however, that it is not also conditioned by factors related to a particular party’s political strategy. The Polish example, therefore, fails to confirm the opposition between the two main conceptions of Euroscepticism – either as determined by ideology or as determined by political strategy.